2011
DOI: 10.1073/pnas.1116683109
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial bioluminescence as a lure for marine zooplankton and fish

Abstract: The benefits of bioluminescence for nonsymbiotic marine bacteria have not been elucidated fully. One of the most commonly cited explanations, proposed more than 30 y ago, is that bioluminescence augments the propagation and dispersal of bacteria by attracting fish to consume the luminous material. This hypothesis, based mostly on the prevalence of luminous bacteria in fish guts, has not been tested experimentally. Here we show that zooplankton that contacts and feeds on the luminescent bacterium Photobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 47 publications
0
30
0
1
Order By: Relevance
“…Previous studies in Chesapeake Bay, a brackish water habitat similar to Oyster Pond, have found the presence of bioluminescence in around 50% of all isolated strains and, based on clustering by phenotypic traits, hypothesized the presence of the lux operon to be an ecologically relevant trait of environmental nontoxigenic branches in the phylogeny of V. cholerae (19,52). The bioluminescence trait has been linked to the colonization of zooplankton, which in an illuminated state makes easy prey for visually oriented predators, thus enabling bioluminescent bacteria to invade the nutrient-rich gut regions of vertebrate predators (19,53). CC1 strains also harbor the ability to take up choline and convert it to betaine (through the action of the betTIBA operon, shared with sister taxa CC2, RC385, and VL426).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in Chesapeake Bay, a brackish water habitat similar to Oyster Pond, have found the presence of bioluminescence in around 50% of all isolated strains and, based on clustering by phenotypic traits, hypothesized the presence of the lux operon to be an ecologically relevant trait of environmental nontoxigenic branches in the phylogeny of V. cholerae (19,52). The bioluminescence trait has been linked to the colonization of zooplankton, which in an illuminated state makes easy prey for visually oriented predators, thus enabling bioluminescent bacteria to invade the nutrient-rich gut regions of vertebrate predators (19,53). CC1 strains also harbor the ability to take up choline and convert it to betaine (through the action of the betTIBA operon, shared with sister taxa CC2, RC385, and VL426).…”
Section: Resultsmentioning
confidence: 99%
“…This research tested the long-held hypothesis that light production acts as a lure for fish and allows the bacterium to gain access to the nutrient-rich fish intestine (Zarubin, Belkin, Ionescu, & Genin, 2012). For example, a recent study explored the role of bioluminescence in the bacterium Photobacterium leiognathi.…”
Section: Fischeri and Bioluminescencementioning
confidence: 99%
“…A recent laboratory study showed that the nocturnal ringtail cardinalfish (Apogon annularis) was more attracted to zooplankton which had fed on luminescent bacteria and subsequently started to glow (Zarubin et al 2012). A field study found catch rates that were 1.2 times as high in tuna, and up to 4.8 times as high in several bottom-dwelling species when a bait dipped in a luminescent solution was used (Makiguchi et al 1980).…”
Section: Insights From Recreational Anglingmentioning
confidence: 99%